2017
DOI: 10.1186/s12888-017-1343-x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring mental well-being in Norway: validation of the Warwick-Edinburgh Mental Well-being Scale (WEMWBS)

Abstract: BackgroundMental well-being is an important, yet understudied, area of research, partly due to lack of appropriate population-based measures. The Warwick-Edinburgh Mental Well-being Scale (WEMWBS) was developed to meet the needs for such a measure. This article assesses the psychometric properties of the Norwegian version of the WEMWBS, and its short-version (SWEMWBS) among a sample of primary health care patients who participated in the evaluation of Prompt Mental Health Care (PMHC), a novel Norwegian mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
61
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 40 publications
9
61
1
Order By: Relevance
“…The response scale ranged from (1) None of the time to (5) All of the time, where higher sum scores indicated higher mental well-being (range 14-70). The WEMWBS has been validated in the general population (2), clinical samples (30), and in adolescents (31)(32)(33). Cronbach's alpha for the scale in the present study was .88 (T1) and .90 (T2).…”
Section: Assessmentsmentioning
confidence: 49%
“…The response scale ranged from (1) None of the time to (5) All of the time, where higher sum scores indicated higher mental well-being (range 14-70). The WEMWBS has been validated in the general population (2), clinical samples (30), and in adolescents (31)(32)(33). Cronbach's alpha for the scale in the present study was .88 (T1) and .90 (T2).…”
Section: Assessmentsmentioning
confidence: 49%
“…Population-level studies support the psychometric properties of the WEMWBS as a measure of mental wellbeing (Clarke et al, 2011;Lloyd & Devine, 2012), including cross cultural studies (Taggart et al, 2013;Trousselard et al, 2016). The WEMWBS is inversely related to measures of common psychopathology assessing symptoms of depression and anxiety (Smith, Alves, Knapstad, Haug, & Aarø, 2017) and is positively related to favourable psychosocial working conditions (Bartram, Yadegarfar, Sinclair, & Baldwin, 2011). In the current study the WEMWBS reported satisfactory reliability α = 0.95.…”
Section: Psychological Wellbeingmentioning
confidence: 88%
“…The outcome variables mental wellbeing, and anxiety and depression symptoms were both included as measures of mental health. A Norwegian translation of the Short Warwick-Edinburgh Mental Well-Being Scale (SWEMWBS) was used to measure mental wellbeing (Smith, Alves, Knapstad, Haug, & Aaro, 2017;Stewart-Brown et al, 2009). The respondents were asked how they had felt about the following positively worded statements over the past two weeks: 1.…”
Section: Mental Healthmentioning
confidence: 99%